A coordination polymer based on dinuclear (pyrazinyl tetrazolate) copper(ii) cations and Wells–Dawson anions for high-performance supercapacitor electrodes. Issue 40 (3rd October 2017) - Wang, Guangning; Chen, Tingting; Li, Shaobin; Pang, Haijun; Ma, Huiyuan
Abstract : A new POM-based coordination polymer was used as supercapacitor electrode showing excellent performance, which can effectively solve the water solubility and low conductivity of traditional POM electrodes. Abstract : A new coordination polymer, (H2 bpe)(Hbpe)2 {[Cu(pzta)(H2 O)][P2 W18 O62 ]}·5H2 O (1 ) (pztaH = 5-(2-pyrazinyl) tetrazolate, bpe = bis(4-pyridyl)ethylene), was synthesized by the hydrothermal method. The structure was determined by single crystal X-ray diffraction analyses and further characterized by the SEM, EDS, BVS, FTIR, and PXRD techniques. In1, the [P2 W18 O62 ] 6− (P2 W18 ) clusters as bidentate connectors link [Cu(pzta)(H2 O)]2 4+ dinuclear copper(ii ) complexes to form inorganic–organic chains. These chains and the [H2 bpe] 2+ counter-cations are fused together via hydrogen bonding to form a 3D supramolecular architecture. While1 was employed as the electrode in a supercapacitor, the cycling stability (90.7% capacitance retention after 1000 circles) and specific capacitance (168 F g −1 at a current density of 5 A g −1 ) of the1 -based electrode are better than those of the parent α-K6 P2 W18 O62 -based electrode, demonstrating more outstanding electrochemical performances of1 . Besides, the1 -based electrode showed excellent electrocatalytic activities towards the reduction of H2 O2 and KIO3 .